Personnel Administration Based on Six Perfections of Administrators in Schools under the Secondary Educational Service Area Office 27 - Tongwisate, Prewina; Thinsandee, Theeraphat; Phansawang, Jiraporn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objective of the research article were 1) to study the current and desired situations of the Personnel Administration based on the Six Perfections, 2) to analyze the needs of the Personnel Administration Using the Six Perfections, 3) to find out the suggestions and recommendations related to the administration of those particular schools by Administrators of the Schools under the Jurisdiction of the Secondary Educational ServiceOffice, Area 27. Samples were the administrators and teachers, totally 347 in number. The tool for collecting the data was the five-rating scale questionnaire. The data collected were analyzed by the computer program, and the statistical devices consisted of frequency, percentage, mean, and standard deviation. The research results were as follows: 1. The current situation of the Personnel Administration Using the Six Perfections by Administrators in the Schools under the Jurisdiction of the Secondary Educational Service Office Area 27was found, both in overall and individual aspects, to be at the ‘MUCH’ level. And the desired situation was found, both in overall and individual aspects, to be at the ‘MOST’ level. 2. The needs index of the Personnel Administration based on the Six Perfections by administrators in the so-said schools was found, in an overall aspect, to be at 0.23 level. 3. The results of the study suggest that 1) Personnel planning (Giving) should survey the lack of necessary information for further planning. 2) The personnel recruitment (Viriya) should follow rules and regulations strictly. 3) The personnel existence (Viriya) should have a meeting to know teachers’ problems in each section. 4) Personnel development (Giving) should encourage people to improve themselves regularly by attending seminars at least once a semester. 5) Personnel Performance Evaluation (Wisdom) Administrators should evaluate teachers’ work using authentic assessment and 6) Personnel retirement (Wisdom), administrators should listen to teacher’s views and carefully make decisions before firing or retiring someone.